Penyuluhan Kesehatan Tentang Kesehatan Jiwa Usia Muda (Remaja) Pendekatan Keluarga Dan Agama Sebagai Preventif Psychosocial Trauma - Tutur Kardiatun; Wida Kuswida Bhakti; Ramadhaniyati Ramadhaniyati; Sri Ariyanti; Tri Wahyuni (Celebes Abdimas: Jurnal Pengabdian Kepada Masyarakat, 2019)
The general objective of community service with Health Education on Young Mental Health (Adolescents) this Family and Religion approach as Psychosocial Trauma is to increase promotive efforts to stimulate the creation of mental health for young people (adolesencents) in LPKA class IIB Sungai Raya by optimizing the role of the family and religious base, is expected to be able to form characteristics of adolesecents who always have strong religious beliefs in thinking and acting, positive thinking, actualizing themselves well, and having a better outlook on life. The PKM method is to use lecture and discussion techniques. The target of this activity is young people (adolesencents) who inhabit LPKA class IIB Sungai Raya Pontianak Regency. The PKM implementing team is a lecturer involving, educational staff and students of the STIK Muhammadiyah Pontianak. The results of the implementation of the PKM showed the enthusiasm of active participants because the theme of health was never known by students in the LPKA class IIB Sungai Raya and the activities took place in an orderly manner. Of the 25 health participants, 80% of participants were able to answer correctly from the 5 questions given during the summative evaluation. an increase in knowledge of the participants about mental health.